La surprenante imagerie médicale de la revue Neuf - Laurence Perrigault (Strenae)
This article examines illustrations in the review Neuf, created by Robert Delpire in 1950 while a medical student, and was originally intended as an artistic periodical for the medical profession. Though the publication was financed by pharmaceutical companies, who were its main advertisers and whose advertisements were sometimes created by Neuf's artists, doctors were soon excluded from the editorial board. The magazine then turned primarily to ethnography and photography. During its four years of existence, Neuf made images its point of pride: photography was valued above all, though cartoons were valued too. Contrary to the literary magazines of the inter-war period—notably those of the Surrealists—and despite prefaces and articles written by famous writers, the review worked hard to promote the status of photographers as authors, on a par with writers.Neuf would become Robert Delpire's springboard to creating his publishing house, which would become famous for its photography books, and would also publish children’s picture books.